Penggunaan Bambu Sebagai Struktur Rumah Tinggal Modern Ramah Gempa - Mirani, Zulfira; Sari, Desnila -; Natalia, Monika; Partawijaya, Yan; Atmaja, Jajang (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2024)
Bamboo material can be applied to structural and decorative elements of modern and minimalist architecture. Use bamboo as structural element, among: 1) as reinforcement structural column, bamboo diameter of 12 cm inserted into the structural column inside iron reinforcement, then cast with concrete. This technique can reduce concrete volume up to 50% than conventional concrete columns, 2) as wall reinforcement, bamboo inserted between the iron reinforcement of the supporting wall, then cast with concrete mortar. This system in addition strengthening walls against the moment forces pressure, can also reduce the volume of concrete. This system can produce walls with a thickness of only 8 cm, much thinner when compared to conventional brick walls 15 cm thick, 3) as reinforcement of concrete slabs, woven bamboo is laid horizontally as a partial replacement for concrete reinforcement iron. This system aims to significantly reduce the amount of iron on the slab, which will reduce construction costs. Science and technology application activities for lecturers of the Department of Civil Engineering, Politeknik Negeri Padag regarding the use of bamboo as earthquake strength for modern residential structure have been carried out at Panti Asuhan Khusus Anak Mentawai, Jl.Purus 4 Padang, on Sunday, August 20, 2023. This activity provides knowledge and adds insight for orphanage children, will finish their education in high school, about alternative materials to replace wood and concrete that are cheaper. So later it is hoped that if they are entrepreneurial or involved in the construction world use of bamboo.